THE IMPLEMENTATION OF GAME-BASED ASSESSMENT FOR LEARNING THROUGH SQUIGABE IN THE MERDEKA CURRICULUM - Ariestiara, Ajeng Rahmadania (Proceeding of International Seminar on Humanity, Education, and Language, 2025)
This study aims to describe the implementation of Squigabe (Squid Game Teks Berita), a form of game-based assessment designed to support Indonesian language learning within the framework of the Merdeka Curriculum. Employing a descriptive qualitative approach, the research analyzes how Squigabe functions as an assessment aligned with the principles of assessment for learning, an assessment approach that not only measures outcomes but also actively and reflectively supports the learning process. Data were collected through observation, interviews, and documentation of junior high school students’ learning activities on news text material. The findings reveal that the application of the game-based assessment Squigabe effectively enhances students’ learning motivation, active engagement, and understanding of the structure and content of news texts. Moreover, game elements such as challenges, levels, and narrative structures proved effective in creating a fun, collaborative, and contextual classroom environment. These findings indicate that assessment can be designed in a creative and humanistic manner while serving as an integral part of a student-centered learning process. This study contributes to innovative assessment practices in Indonesian language education that are relevant to the demands of 21st-century learning.